GEOLOGICAL, GEOARCHAEOLOGICAL, BIOLOGICAL, AND HISTORICAL HERITAGE OF LENGGONG GEOPARK DEVELOPMENT - Talib, Nor Khairunnisa; Said, Mohd Zulhafiz; Abdullah, Nurazlin; Masnan, Syeh Sahibul Karamah; Rashidi, Nurasikin; Saidin, Mokhtar; Komoo, Ibrahim; Ali, Che Aziz; Ahmad, Norhayati; Hussin, Rosazman (PLANNING MALAYSIA, 2022)
The Lenggong Valley is uniquely significant in national and international geological heritage and was declared a UNESCO Archaeological Heritage Site in 2012. The Lenggong Valley was formed 550 million years ago. It is one of the oldest in Peninsular Malaysia, equivalent to the rock formations in Langkawi and Jerai. The geological evolution in the Lenggong Valley also produced biodiversity and the history of early human prehistoric to the present time. Due to this privilege, the Lenggong Geopark nomination development effort started in 2020 by forming the Geopark Promotion and Development Committee. Lenggong Geopark covers an area of 2,068 km2 (enclosed by the boundaries of the Lenggong Parliament). A total of 27 geosites have been identified, depicting four important geological and historical tectonic evolutions and special geomorphic features in the Lenggong Valley. Eight biosites are still preserved, involving granite mountain, limestone, and lowland ecosystems covered by different forest types. It is the limestone hills that contain a large number of rare and endemic flora species. In addition, eight geoarchaeological sites were also identified that depicts the interaction between early humans and the geological landscape. The unique and preserved traditions of life, art and culture have added value to the geopark. Therefore, active efforts continue to be carried out in the development of geosites and programs with the local community to foster a high sense of pride and belonging to a place, in addition to an understanding of the preservation and conservation of natural and cultural heritage in Lenggong Geopark. Various activities based on tourism activities are also planned to stimulate the economy and introduce Lenggong as the second national geopark area in the State of Perak.